STUDENTS’ PROBLEMS IN MAKING DERIVATIONAL WORDS - Setyani, Dwi Putri; Hartono, Rudi; Priyatmojo, Arif Suryo (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2017)
This paper aims to find out what kinds of errors the students made in making derivational words and the most frequent errors occurred. It is a descriptive qualitative research which focuses on the error analysis of derivational morphology. The subject of this study was the students of English Education UNNES batch 2012. By using quota sampling, 25 students were taken for the try-out test and another 25 students were taken for the real test. The data were obtained from a test and questionnaire. In analyzing the data, the researcher used error analysis method. It consists of identifying errors, describing errors, explaining errors and error evaluation. The finding errors were analyzed based on the Surface Structure Taxonomy that specifies four types of errors namely omission, addition, misordering and misformation. The result showed that errors were found in all categories of derivational morphology. There were 146 errors which consisted of 98 (67,1%) misformation, 34 (23,3%) omission, and 14 (9,6%) addition. Thus, it was crystal clear that the most frequent errors occurred in misformation.